Identifikasi Benih Melalui Citra Digital dan Karakterisasi Morfo-fisiologi Kecambah Melon Hibrida Salfa F1 IPB - Agustin; Abdul Qadir; Astryani Rosyad; MR Suhartanto (Jurnal Agroekoteknologi dan Agribisnis, 2026)
Melon (Cucumis melo L.) is a high-value horticultural commodity with an increasing market demand. This condition requires the availability of high-quality seeds to support optimal productivity and fruit quality. Therefore, a rapid, accurate, and non-destructive method for seed characterization is needed to support seed quality assesment. This study aimed to characterize Salfa F1 hybrid melon seeds using a digital imaging approach and to evaluate their morphophysiological characteristics  based on imbibition, germination, and vigor. The research was conducted at the Seed Biology and Reproduction Laboratory, Department of Agronomy and Horticulture, IPB University, from September to November 2025. The results showed that Salfa F1 melon seeds exhibited relatively homogeneous morphological characteristics based on  area, perimeter, and shape parameters (circularity, aspect ratio, and solidity). The imbibition pattern showed a nonlinier  response over time, with the qubic regression model providing a high level of fit to the observed data. In line with the imbibition pattern, the high germination percentage and vigor index indicated good physiological testing can provide complementary information for characterizing the morphophysiological quality of Salfa F1 melon seeds.